School Nursing Protocol for the Management of Human Bites. (November 2019) - Collins, Ruth; Wallin, Robin; Park, Katherine
Human biting is considered a common stage in pediatric infant growth and development. However, this stage is not considered appropriate once children enter group daycare and school settings, and such behavior can lead to injury, stress, and trauma for other students and staff. When biting occurs in the school setting, staff are often unprepared to respond appropriately, and may seek delayed care, if at all. The school nurse may also be ill-equipped to provide first aid and education if there are no standardized guidelines to follow. Having a protocol in place for human bite incidents in the school setting helps school nurses provide information to students, parents, and staff in a timely manner and assists them with following evidence-based practice. Accurate documentation of the incidents also allows school nurses to identify triggers and knowledge deficits, which can assist them in planning educational interventions and training in the school setting.